The VACCINES Act: Deciphering Vaccine Hesitancy in the Time of COVID-19 - McAteer, John (Clin Infect Dis, 2020)
Since the COVID-19 pandemic first hit Wuhan, China, in December 2019, scientists have been racing to develop and test novel vaccines to protect against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The speed of scientific discovery related to COVID-19 is unprecedented. With several vaccine candidates already being tested in clinical trials, we pose the question: what will the vaccine hesitant do in the face of this pandemic?